Mechanotransduction of autotransplants: remodeling potential of heart valves from autologous pericardial tissue - Steitz, Marvin; Khan, Mahamuda Badhon; Breitenstein-Attach, Alexander; Warnack, Boris; Edelmann, Frank; Berger, Felix; Schmitt, Boris (Frontiers in Bioengineering and Biotechnology, 2025)
Current commercial heart valve prostheses are non-living structures, either derived from artificial materials (mechanical valves) or foreign biological materials (xeno- or homo-graft). Since the use of viable tissue with native-like properties is essential for a heart valve with self-regulation properties, autologous collagen-based tissue can be considered a promising alternative material. While the extracellular matrix of pericardial tissue offers a solid foundation, it is the interstitial cells that play a crucial role in ensuring long-term durability. This review explores the mechanotransduction capabilities of autologous tissue as a replacement material for living heart valves with regenerative potential.